Estudos funcionais e biofísicos de uma fosfolipase A2 isolada da peçonha da serpente Bothrops alternatus - Eulálio, Micaela de Melo Cordeiro (2020)
Snakes of the Bothrops genus are of great scientific, medical and social interest in Brazil, because they are responsible for the largest number of snakebites that occurrences in the country. Toxins isolated from snake venoms have several biological activities and are classified in different classes, one being phospholipases A2 (PLA2), which can cause a variety of physiological changes when inoculated in organisms. This study aimed to isolate, characterize and evaluate the biological functions of a PLA2 (BaltAc-PLA2) from the crude venom of the snake Bothrops alternatus, popularly known as urutu-cruzeiro. The purification of this toxin was performed using two chromatography steps (anion exchange and reverse phase). With the intention to verify the purity of the samples obtained in the liquid chromatography experiments, polyacrylamide gels (SDS PAGE) at 12% (w/v) were performed. Mass spectrometry, Circular Dichroism Spectroscopy and Dynamic Light Scattering tests were performed to physico-chemical characterization the isolated toxin. The catalytic action of the toxin was evaluated spectrophotometrically using the substrate Diheptanoyl Thio-PC and indirectly, with erythrocytes and egg yolk. In addition, three potential inhibitors were evaluated: varespladib, suramine and rosmarinic acid. The potential oxidizing effect of BaltAc-PLA2 on hemoglobin solutions (SolHb) was performed using microplate reader (Multiskan GO) in wavelengths of 540 and 630 nm. To assess the coagulant activity, readings were made using the Coagmaster 2.0 (Wama) equipment. BaltAc-PLA2 is an acidic character and catalytically active protein, with an approximate molecular mass of 14 kDa estimated by SDS PAGE. The analysis of ion fragments by MS / MS showed an amino acid sequence from the catalytic site CCFVHDCCYGK, presenting homology with several PLA2 of acid character present in venoms of snakes of the genus Bothrops. Structural studies using this PLA2 can assist in the development of new therapeutic agents, for possessing high scientific and technological potential.